2019
DOI: 10.1161/strokeaha.119.025950
|View full text |Cite
|
Sign up to set email alerts
|

Training for Walking Efficiency With a Wearable Hip-Assist Robot in Patients With Stroke

Abstract: Background and Purpose— The purpose of this study was to investigate the effects of gait training with a newly developed wearable hip-assist robot on locomotor function and efficiency in patients with chronic stroke. Methods— Twenty-eight patients with stroke with hemiparesis were initially enrolled, and 26 patients completed the randomized controlled trial (14 in the experimental and 12 in the control groups). The experimental group participated in a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 29 publications
1
96
0
1
Order By: Relevance
“…Increased activity in SMC and SMA in the late phase during walking without the GEMS-H may indicate a compensatory activation in stroke patients due to impaired brain function and loss of automatism. Our previous study [10] demonstrated that the GEMS-H enhanced symmetricity of gait in stroke patients. Less activation in the SMC and SMA in the late phase during gait with GEMS-H might be a re ection of more symmetric and coordinated gait patterns by assisting rhythmic hip exion and extension movements in gait with the GEMS-H.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Increased activity in SMC and SMA in the late phase during walking without the GEMS-H may indicate a compensatory activation in stroke patients due to impaired brain function and loss of automatism. Our previous study [10] demonstrated that the GEMS-H enhanced symmetricity of gait in stroke patients. Less activation in the SMC and SMA in the late phase during gait with GEMS-H might be a re ection of more symmetric and coordinated gait patterns by assisting rhythmic hip exion and extension movements in gait with the GEMS-H.…”
Section: Discussionmentioning
confidence: 93%
“…The GEMS-H has a lightweight (2.8 kg), comfortable and slim design that can be adjusted to t the user's body (Figure 1). For more information regarding the strategy of assistive algorithms used for the GEMS-H, please see our previous paper [10].…”
Section: Wearable Hip-assist Robot Gems-hmentioning
confidence: 99%
See 1 more Smart Citation
“…The GEMS-H has a lightweight (2.8 kg), comfortable and slim design that can be adjusted to fit the user's body. For more information regarding the strategy of assistive algorithms used for the GEMS-H, please see our previous paper [10].…”
Section: Wearable Hip-assist Robot Gems-hmentioning
confidence: 99%
“…The Gait Enhancing and Motivating System-Hip (GEMS-H), developed by Samsung Electronics Co., Ltd. (Suwon, Republic of Korea), is a hip-type robotic exoskeleton. Our previous studies showed that GEMS-H improved gait function, muscle efficiency, and cardiopulmonary metabolic efficiency [7][8][9][10]. However, it is not yet known how GEMS-H assisted gait training modulates cortical activity of stroke patients.…”
Section: Introductionmentioning
confidence: 99%